The Situational Prevention of Terrorism: An Evaluation of the Israeli West Bank Barrier - Perry, Simon (Journal of quantitative criminology, 2017)
Objectives: Informed by situational crime prevention (SCP) this study evaluates the effectiveness of the 'West Bank Barrier' that the Israeli government began to construct in 2002 in order to prevent suicide bombing attacks. Methods: Drawing on crime wave models of past SCP research, the study uses a time series of terrorist attacks and fatalities and their location in respect to the Barrier, which was constructed in different sections over different periods of time, between 1999 and 2011. Results: The Barrier together with associated security activities was effective in preventing suicide bombings and other attacks and fatalities with little if any apparent displacement. Changes in terrorist behavior likely resulted from the construction of the Barrier, not from other external factors or events. Conclusions: In some locations, terrorists adapted to changed circumstances by committing more opportunistic attacks that require less planning. Fatalities and attacks were also reduced on the Palestinian side of the Barrier, producing an expected 'diffusion of benefits' though the amount of reduction was considerably more than in past SCP studies. The defensive roles of the Barrier and offensive opportunities it presents, are identified as possible explanations. The study highlights the importance of SCP in crime and counter-terrorism policy.